THE EFFECT OF FINANCIAL RATIOS ON STOCK PRICE IN LQ45 - Nita Priska Ambarita (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The stock price is the most important thing. This study aims to determine the effect of financial performance as reflected in financial ratios on the company's stock price. The results of this study indicate that the line of business of a company can influence investor behavior which has an impact on its stock price. profitability has a significant negative effect on stock prices of the main sectors, and no significant negative effect on the manufacturing sector and the service sector (non-banking). Leverage has a significant positive effect on company stock prices in the main sectors, the manufacturing sector and the service sector (non-banking). Market Ratio has no significant positive effect on stock prices of main sector companies, significant positive on stock prices of manufacturing sector companies and a significant negative effect on stock prices of service sector companies (non-banking) and activities have no significant positive effect on stock prices of main sector companies, and negatively significant in the manufacturing and services (non-banking) sectors.